2019
DOI: 10.1021/acsnano.9b04149
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Photovoltaic Responses in 3D Radial Junction Solar Cells Revealed by High Spatial Resolution Laser Excitation Photoelectric Microscopy

Abstract: The actual light absorption photovoltaic responses realized in three-dimensional (3D) radial junction (RJ) units can be rather different from their planar counterparts and remain largely unexplored. We here adopt a laser excitation photoelectric microscope (LEPM) technology to probe the local light harvesting and photoelectric signals of 3D hydrogenated amorphous silicon (a-Si:H) RJ thin film solar cells constructed over a Si nanowire (SiNW) matrix, with a high spatial resolution of 600 nm thanks to the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…Helical SiNWs can also be designed as axial or radial junction solar cells, which can give full play to the electrical advantages of SiNWs and be used as micro power supply in electrical components. 35,36 In addition, in the calculation process of this work, it is also found that helical SiNWs have the selectivity of polarized light, which is similar to other helical nanowire structures and can be used in optical devices.…”
Section: View Article Onlinementioning
confidence: 57%
“…Helical SiNWs can also be designed as axial or radial junction solar cells, which can give full play to the electrical advantages of SiNWs and be used as micro power supply in electrical components. 35,36 In addition, in the calculation process of this work, it is also found that helical SiNWs have the selectivity of polarized light, which is similar to other helical nanowire structures and can be used in optical devices.…”
Section: View Article Onlinementioning
confidence: 57%
“…Recently, a laser excitation photoelectric microscope (LEPM) technology has been adopted by H. Zhang et al to directly detect the local light-harvesting behavior and photoelectric signals of RJ units with a smaller size of 4 μm wide, [149] as presented in Figure 9a, as and d) corresponding signal intensity. [149] Copyright 2019 American Chemical Society.…”
Section: Nanoscale Photovoltaic Responses In Rj Unitsmentioning
confidence: 99%
“…These systems are characterized by an efficient photo induced downhill energy transfer from the nanostructured material to the dyes, and in this field the term antenna commonly refers to this behavior [ 36–39 ] and not to antenna or resonant modes as it is used in the photovoltaic field. [ 40,41 ] In particular, Si nc has been studied obtaining energy transfer efficiencies of 65% generally by using chromophores concentrations of a few m m , with the perspective of increment by functionalization procedure. [ 32 ]…”
Section: Figurementioning
confidence: 99%